PELATIHAN DESAIN PEMBELAJARAN BIOLOGI SMA BERORIENTASI LITERASI SAINS - Faisal, Faisal; Adnan, Adnan; Bahri, Arsad; Saleh, Andi Rahmat; Saparuddin, Saparuddin (Jurnal Abdi Negeriku, 2022)
In recent years, many government initiatives in the field of education have been directed at developing curriculum and learning systems that emphasize students' scientific literacy skills. This community partnership program (PKM) aims to improve biology teachers' understanding of scientific literacy competencies and how to design science literacy-oriented learning. We selected a group of ten high school biology teachers (five groups) as the target subjects of the PKM program. PKM activities are designed for six months (May to November 2022), with a variety of topics and activities, including individual and group assignments, discussions, and presentations, both online (Zoom) and face-to-face. During PKM activities, biology teachers have the opportunity to explore the conceptual framework of several models or learning approaches that are science literacy-oriented. Groups of biology teachers also practice designing learning stages for each of the models or approaches that have been chosen. The learning models or approaches chosen by teachers during PKM activities vary, including project-based learning, STEM education, science process skills approaches, differentiated learning, and social-scientific issues-oriented learning. The resulting learning design shows that the PKM program helps teachers improve their knowledge of science literacy-oriented biology learning.